2017
DOI: 10.2337/dc17-0238
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Environmental Interactions Modify the Risk of Diabetes-Related Autoimmunity by 6 Years of Age: The TEDDY Study

Abstract: OBJECTIVEWe tested the associations between genetic background and selected environmental exposures with respect to islet autoantibodies and type 1 diabetes.RESEARCH DESIGN AND METHODSInfants with HLA-DR high-risk genotypes were prospectively followed for diabetes-related autoantibodies. Single nucleotide polymorphisms (SNPs) came from the Illumina ImmunoChip and environmental exposure data were by parental report. Children were followed to age 6 years.RESULTSInsulin autoantibodies occurred earlier than GAD an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
162
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 167 publications
(184 citation statements)
references
References 18 publications
19
162
2
1
Order By: Relevance
“…SNP variants that showed the strongest positive change with increased islet autoimmunity in our ranking method were linked to PTPN22, INS, SH2B3, ERBB3, RNLS and IL2RA. Variants in these genes were previously associated with the development of autoantibodies, disease development and progression from presenting with autoantibodies to type 1 diabetes onset in at-risk individuals [12,[22][23][24][25][26]. However, how these SNPs exactly contribute to increased T cell autoimmunity is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…SNP variants that showed the strongest positive change with increased islet autoimmunity in our ranking method were linked to PTPN22, INS, SH2B3, ERBB3, RNLS and IL2RA. Variants in these genes were previously associated with the development of autoantibodies, disease development and progression from presenting with autoantibodies to type 1 diabetes onset in at-risk individuals [12,[22][23][24][25][26]. However, how these SNPs exactly contribute to increased T cell autoimmunity is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The typical natural history of type 1 diabetes in children is the appearance of the first high‐affinity autoantibody , which is usually IAA in the youngest children, followed by the appearance of other islet autoantibodies , usually within 3 years , and eventually the development of diabetes. Two islet‐autoimmunity endotypes are distinguished . One is characterized by the first appearance of IAA in children carrying HLA‐DR4, and occurs in the first years of life.…”
Section: Historical Perspectivesmentioning
confidence: 99%
“…We also examined secondary outcomes of IAA only or GADA only as the first appearing autoantibody (IAA‐first IA and GADA‐first IA, respectively). Previously published studies in TEDDY have showed a relationship between the order of autoantibody appearance and risk of T1D …”
Section: Methodsmentioning
confidence: 99%
“…Previously published studies in TEDDY have showed a relationship between the order of autoantibody appearance and risk of T1D. [19][20][21][22] The infant screening form completed by the family at birth provided basic demographic information and family history of diabetes. TEDDY has previously reported some concordance between national recommendations and the prevalence of prenatal vitamin D and n-3 FA supplement use among TEDDY mothers.…”
Section: Methodsmentioning
confidence: 99%